MATH SOLVE

4 months ago

Q:
# 10ac-x/11=-3 solve for a

Accepted Solution

A:

1) You'll have to get raid of the fraction by multiplying 10ac by 11, x/11 by 11 which the 11's cancels out and -3 multiplied by 11 .

2)Now you have 10ac -x = -33. Add x on both sides of the equal sign you get 10ac = -33 + x

3) Divide both sides by 10c to get "a" by itself, so "a" = -33+x divided by 10c

2)Now you have 10ac -x = -33. Add x on both sides of the equal sign you get 10ac = -33 + x

3) Divide both sides by 10c to get "a" by itself, so "a" = -33+x divided by 10c